Development of fire-protective water-borne intumescent coating incorporated with rubberwood ash for steel - Beh, Jing Han (2022)
This research was carried out to study the re-use of a type of agricultural by-product as natural substitute of mineral fillers in the fire-protective water-borne intumescent coating. This research aims to explore the potential use of natural agricultural waste in the intumescent coating, with effort to minimise the reliance on exotic industrial fillers and work towards conserving the environment in a more sustainable way along with SDG 17 goals. Rubberwood biomass ash (BioAsh), which was derived from the combustion of rubberwood biomass in a fuel factory, was obtained for reuse as a natural mineral filler substitute in water-based intumescent coatings. The specific surface area of the BioAsh was 3.10 m2/g, with the particle’s surface areas predominant composed of mesopores, which was justified using the BrunauerEmmett-Teller Test (BET). BioAsh coatings (BAIC) formulated with 3.5 wt% BioAsh exerted the most homogenous and durable surface matrix in the Freeze-thaw cycle test (FCT). Fireresistant test (FRT) and thermogravimetric analysis (TGA) demonstrated the incorporation of the BioAsh with the intumescent flame-retardant formulation, generated positive effects in equilibrium end temperature, thermal decomposition, and weight loss reductions. These effects are most prominent in the BAIC 3-5, which was comprised of 3.5 wt% BioAsh, and 50/40/6.5 wt% vinyl acetate (VA)/intumescent flame retardant additive (IFRA)/ pigment. The BAIC 3-5 showed the lowest equilibrium end temperature at 112.5 C, the lowest thermal degradation at 70.52 wt%, and the highest carbonaceous char formation at 1 3 0 mm. The Surface Electron . Microscopy (SEM) and Energy Dispersive X dense, compact, and coherent char formRay Spectroscopy (EDX) results exhibited a ation for the BAIC 3 supported by the evidence from Fourier-- 5 sample. These results are Transform Infrared Spectroscopy (FTIR), and X Diffractometer (XRD), which revealed the stretching of the OH, PO-- Ray C, and P=O molecular functional groups, and the pr 5. These results revealed esence of thermally stable phosphate compounds in the BAIC 3an appropriate amount of 3.5 wt% renewable BioAsh incorporated as natural mineral fillers substitute in the intumescent coating could lead to a better fire resistance an d mechanical properties to protect steel structures from fire.